2020
DOI: 10.1002/agj2.20449
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and nutrient accumulation and partitioning of fall‐winter safflower in a double‐cropping system of southeastern Brazil

Abstract: The quantification of nutrient uptake and partitioning during crop cultivation, as well as nutrients removed at harvest, are essential information to optimize nutrient management. A 2‐yr field experiment was conducted in Botucatu, São Paulo State, southeastern Brazil, to examine the biomass accumulation and nutritional requirements and removal of two safflower (Carthamus tinctorius L.) genotypes cultivated in the fall‐winter season of a double‐cropping system. Seven plant samplings were performed during the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…According to Koc (2019) winter survival rates varied between 1.25% and 40.7% at −14.2°C without a snow cover in standard safflower varieties (Remzibey, Dincer, Balci and Linas), whereas in winter‐tolerant genotypes this rate was between 94.0% and 99.5%. Many studies have shown that safflower can be grown as a winter crop in regions with mild temperatures or as a spring crop in cold regions (Abou Chehade et al, 2022; Guidorizzi et al, 2021; Koutroubas et al, 2004). The local safflower cultivars grown in Turkey are sown in late winter or early spring and flower rapidly without over‐wintering.…”
Section: Introductionmentioning
confidence: 99%
“…According to Koc (2019) winter survival rates varied between 1.25% and 40.7% at −14.2°C without a snow cover in standard safflower varieties (Remzibey, Dincer, Balci and Linas), whereas in winter‐tolerant genotypes this rate was between 94.0% and 99.5%. Many studies have shown that safflower can be grown as a winter crop in regions with mild temperatures or as a spring crop in cold regions (Abou Chehade et al, 2022; Guidorizzi et al, 2021; Koutroubas et al, 2004). The local safflower cultivars grown in Turkey are sown in late winter or early spring and flower rapidly without over‐wintering.…”
Section: Introductionmentioning
confidence: 99%